ADAM17 is essential for ectodomain shedding of the EGF‐receptor ligand amphiregulin. Issue 4 (12th March 2018) - Hosur, Vishnu; Farley, Michelle L.; Burzenski, Lisa M.; Shultz, Leonard D.; Wiles, Michael V.
Abstract : The epidermal growth factor (EGF)‐receptor ligand amphiregulin (AREG) is a potent growth factor implicated in proliferative skin diseases and in primary and metastatic epithelial cancers. AREG, synthesized as a propeptide, requires conversion to an active peptide by metalloproteases by a process known as ectodomain shedding. Although (ADAM17) a disintegrin and metalloprotease 17 is a key sheddase of AREG, ADAM8‐, ADAM15‐, and batimastat (broad metalloprotease inhibitor)‐sensitive metalloproteases have also been implicated in AREG shedding. In the present study, using a curly bare ( Rhbdf2 cub ) mouse model that shows loss‐of‐hair, enlarged sebaceous gland, and rapid cutaneous wound‐healing phenotypes mediated by enhanced Areg mRNA and protein levels, we sought to identify the principal ectodomain sheddase of AREG. To this end, we generated Rhbdf2 cub mice lacking ADAM17 specifically in the skin and examined the above phenotypes of Rhbdf2 cub mice. We find that ADAM17 deficiency in the skin of Rhbdf2 cub mice restores a full hair coat, prevents sebaceous gland enlargement, and impairs the rapid wound‐healing phenotype observed in Rhbdf2 cub mice. Furthermore, in vitro, stimulated shedding of AREG is abolished in Rhbdf2 cub mouse embryonic keratinocytes lacking ADAM17. Thus, our data support previous findings demonstrating that ADAM17 is the major ectodomain sheddase of AREG. Abstract : The curly bare ( Rhbdf2 cub/cub ) mouse mutation induces enhanced secretion of amphiregulin (AREG) to cause hair loss. To determine whether the metalloprotease ADAM17 mediates AREG secretion and the loss‐of‐hair phenotype, we generated Rhbdf2 cub/cub mice deficient in ADAM17 in the skin. Deletion of ADAM17 restores the normal skin phenotype in Rhbdf2 cub/cub mice, suggesting that ADAM17 is essential for AREG secretion in Rhbdf2 cub/cub mice.